Effects of heated water-based exercise on blood pressure: a systematic review - Ngomane, Awassi Yuphiwa; Abreu, Raphael Martins De; Ciolac, Emmanuel Gomes (Pontifícia Universidade Católica do Paraná, 2018)
AbstractIntroduction: Systemic arterial hypertension is one of the main cardiovascular risk factors affecting several population. In this context, heated water-based exercise has emerged as a potential alternative to land- based physical exercise to reduce blood pressure (BP) in hypertensive patients.Objective: To systematically synthesize evidence for the lowering effects of heated water-based exercise on BP in a non-specific population.Methods: Scielo, Pubmed and Scopus electronic databases were searched for studies from 2005 to 2016, with the following descriptors in English: “blood pressure, exercise, immersion, blood pressure and hydrotherapy”. A total of 10,461 articles were found and, after applying the inclusion and exclusion criteria, 13 articles were selected and included in the final analysis. All included articles evaluated individuals from different populations and age groups, submitted to a heated water-based exercise session and/or program.Results: The results suggest that both an acute single session and chronic training period (12 to 24 weeks) of heated water-based exercise may reduce BP in different populations (normotensive, hypertensive, postmenopausal women, and heart transplant populations). The magnitude and duration of acute and chronic hypotensive effect of exercise ranged substantially, which was probably due to the variety of exercise frequency, duration and intensity, as well as due to the studied population.Conclusion: These results suggest that heated water-based exercise may promote acute and chronic hypotensive effects in different populations. However, there is no homogeneity in the protocols used, which may have led to the heterogeneity in magnitude and duration of BP reductions.

ResumenIntroducción:La hipertensión arterial sistémica es uno de los principales factores de riesgo cardiovascular que afecta diferentes poblaciones. Siendo así, el ejercicio físico en piscina calentada ha surgido como una alternativa potencial al ejercicio físico en suelo para la reducción de la presión arterial (PA) de pacientes hipertensos.Objetivo:Revisar la evidencia de los efectos del ejercicio físico en la piscina calentada en la reducción de la PA en poblaciones no específicas.Métodos:Buscamos las bases de datos electrónicas Scielo, Pubmed y Scopus, de 2005 a 2016, con los siguientes descriptores en inglés: “presión arterial, ejercicio, inmersión, presión arterial e hidroterapia”. Se encontraron 10461 artículos y, después de la aplicación de los criterios de inclusión y exclusión, fueron seleccionados 13 artículos que fueron parte del análisis final. Todos los artículos incluidos evaluaron individuos de diferentes poblaciones en diferentes grupos de edad sometidos a programas de ejercicios físicos acuáticos.Resultados:Los resultados sugieren que el ejercicio físico realizado en una piscina calentada puede llevar a diferentes respuestas en la presión arterial, dependiendo de la frecuencia, la duración y la intensidad de las sesiones.Conclusión:Estos resultados sugieren que el ejercicio realizado en una piscina calentada durante 12 a 24 semanas de entrenamiento puede promover efectos benéficos sobre la reducción de la PA. Por otra parte, la sesión aguda no es suficiente para causar un efecto hipotensor. Sin embargo, no hay homogeneidad en los protocolos utilizados, lo que puede haber llevado la divergencia en los resultados.

ResumoIntrodução:A hipertensão arterial sistêmica (HAS) é um dos principais fatores de risco cardiovasculares que afeta diferentes populações. Sendo assim, o exercício físico em piscina aquecida tem surgido como uma potencial alternativa ao exercício físico em solo para a redução da pressão arterial (PA) de indivíduos hipertensos.Objetivo:Revisar a evidência dos efeitos do exercício físico em piscina aquecida na redução da PA em populações não especificas.Métodos:Foram pesquisadas as bases de dados eletrônicas Scielo, Pubmed e Scopus, de 2005 a 2016, com os seguintes descritores em inglês: “pressão arterial, exercício, imersão, pressão arterial e hidroterapia”. Foram encontrados 10.461 artigos e, após a aplicação dos critérios de inclusão e exclusão, foram selecionados 13 artigos que fizeram parte da análise final. Todos os artigos incluídos avaliaram indivíduos de diferentes populações, em diferentes faixas etárias, submetidos a uma sessão e/ou programa de exercícios físicos em piscina aquecida.Resultados:Os resultados sugerem que uma sessão aguda de exercício físico em piscina aquecida, bem como um programa de treinamento de 12 a 24 semanas, pode reduzir a pressão arterial em diferentes populações (normotensos, hipertensos, mulheres na pós-menopausa e transplantados cardíacos). Houve uma grande variação na magnitude e duração do efeito hipotensivo do exercício, o que pode ter sido devido à grande variação de frequência, duração e intensidade das sessões, bem como de populações estudadas.Conclusão:Estes resultados sugerem que o exercício físico em piscina aquecida pode ter efeito hipotensivo agudo e crônico em diferentes populações. No entanto, não há homogeneidade nos protocolos utilizados, o que pode ter levado à heterogeneidade na magnitude e duração das reduções de PA.
Efecto del ejercicio en piscina climatizada sobre la presión arterial: una revisión sistemática
Efeito do exercício em piscina aquecida sobre a pressão arterial: uma revisão sistemática
Keywords: Blood Pressure; Exercise; Hydrotherapy; Hypertension; Immersion; Pressão Arterial; Exercício; Hidroterapia; Hipertensão; Imersão